2018
DOI: 10.3233/jad-180688
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic Correlates of Psychiatric Symptoms in Alzheimer’s Disease

Abstract: Clarifying the relationships between neuropsychiatric symptoms and Alzheimer's disease (AD)-related pathology may open avenues for effective treatments. Here, we investigate the odds of developing neuropsychiatric symptoms across increasing burdens of neurofibrillary tangle and amyloid-β pathology. Participants who passed away between 2004 and 2014 underwent comprehensive neuropathologic evaluation at the Biobank for Aging Studies from the Faculty of Medicine at the University of São Paulo. Postmortem intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 113 publications
9
127
3
Order By: Relevance
“…For example, history of sleep disruption was associated with increased neurofibrillary tangles in the brainstem nuclei known to regulate sleep‐wake process in a postmortem sample of patients with early AD (Braak stage I/II). In a different study, older adults with MCI had increased sleep symptoms, as well as decreased objectively measured sleep continuity and more fragmented sleep independent of neurocognitive performance, suggesting that sleep disruption could be an early marker of neurodegeneration …”
Section: Discussionmentioning
confidence: 99%
“…For example, history of sleep disruption was associated with increased neurofibrillary tangles in the brainstem nuclei known to regulate sleep‐wake process in a postmortem sample of patients with early AD (Braak stage I/II). In a different study, older adults with MCI had increased sleep symptoms, as well as decreased objectively measured sleep continuity and more fragmented sleep independent of neurocognitive performance, suggesting that sleep disruption could be an early marker of neurodegeneration …”
Section: Discussionmentioning
confidence: 99%
“…Anor et al reported greater delusions with right frontal WMH volume in AD. Delusions have been associated with later Braak staging V/VI (Ehrenberg et al, 2018) suggesting that these symptoms are more likely to present in the late stages of AD. GM atrophy and WMH burden in these regions may contribute to the disruption of connectivity in frontotemporal networks.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while protein aggregates are thought to trigger neural degeneration in other brain regions, the LC appears to be spared from frank cell death until mid to late stages of disease, when up to 80% of its cell bodies are lost ( German et al, 1992 ; Busch et al, 1997 ; Zarow et al, 2003 ; Theofilas et al, 2017 ). Furthermore, AD and PD share many comorbidities associated with LC dysfunction, such as exaggerated stress response and anxiety ( Teri et al, 1999 ; Pietrzak et al, 2015 ; Schrag and Taddei, 2017 ), attentional deficits ( Rizzo et al, 2000 ; Berardi et al, 2005 ; Dujardin et al, 2013 ), fatigue and reduced arousal ( Hamann et al, 2000 ; Kelberman and Vazey, 2016 ) and sleep disturbances ( Yesavage et al, 2004 ; Ju et al, 2013 ) that appear time-locked with development of LC pathology ( Busch et al, 1997 ; Grinberg et al, 2010 ; Ehrenberg et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%